COVID-19 and syphilis co-dynamic analysis using mathematical modeling approach - Teklu, Shewafera Wondimagegnhu; Terefe, Birhanu Baye (Frontiers in Applied Mathematics and Statistics, 2023)
In this paper we have proposed and analyzed a new COVID-19-syphilis co-infection mathematical model with ten distinct classes of human population (COVID-19 protected, syphilis protected, susceptible, COVID-19 infected, COVID-19 isolated with treatment, syphilis asymptomatic infected, syphilis symptomatic infected, syphilis treated , COVID-19 and syphilis co-infected, COVID-19 and syphilis treated) which describes COVID-19 and syphilis co-dynamics. We have calculated all the disease-free and endemic equilibrium points of single infections and co-infection models. The basic reproduction numbers of COVID-19, syphilis, and COVID-19 and syphilis co-infection models were determined. The results of the model analyses shown that, the COVID-19 and syphilis co-infection spreading is under control whenever its basic reproduction number is less than unity. Moreover, whenever the co-infection basic reproduction number is greater than unity the COVID-19 and syphilis co-infection propagates throughout the community. The numerical simulations performed by MATLAB code using ode45 solver justified the qualitative results of the proposed model. Moreover, both the qualitative and numerical analyses findings of the study have shown us protections and treatments have fundamental effects on the COVID-19-syphilis co-dynamic disease transmission prevention and controlling in the community.